Pengaruh Multimedia Pada Pembelajaran Terpadu Terhadap Hasil Belajar Matematika Siswa Sekolah Dasar - Damayanti, Putri Surya; Putra, Angga; Pujiarti, Titi; Mariati, Mariati (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to determine the effect of multimedia in integrated learning on mathematics learning outcomes in fourth grade elementary school students. This research uses a quantitative Meta Analysis method, this research uses calculations using effect size analysis techniques. The sample taken was 15 students at SDN Inpres Sambitangga to determine the effect of multimedia in integrated learning on student learning outcomes in mathematics subjects in elementary schools. The calculated effect size result was 0.7 and looking at the interpretation of the effect size, it was included in the medium category. It was concluded that the application of multimedia in integrated learning on mathematics learning outcomes had a moderate influence on fourth grade elementary school students.